Cyclotriphosphazene and tricarbazole based microporous hyper-crosslinked conjugated polymer for CCUS: Exceptional CO2 selectivity and high capacity CO2, CH4, and H2 capture. (January 2023) - Sadak, Ali Enis; Cucu, Evren; Hamur, Beyza; Ün, İlker; Altundas, Ramazan
Abstract: The most significant point in the synthesis of a hyper-crosslinked polymer with high CO2 adsorption and high selectivity properties to be used in carbon capture, utilization and storage (CCUS) is to choose the most compatible core and linker. These should allow the polymer to be synthesized in a single step under the mildest conditions with the highest yield. Here, the synthesis of microporous hyper-crosslinked conjugated polymer EBE-06 was achieved by a single step reaction of hexachlorocyclotriphosphazene and 1, 3, 5-tri(9 H -carbazol-9-yl)benzene with an AlCl3 catalyzed Friedel-Crafts reaction. After being characterized using spectroscopic and analytical techniques, the gas uptake (CO2, CH4, O2, CO and H2 ) and selectivity properties (CO2 /N2, CO2 /CH4, CO2 /O2 and CO2 /CO) of EBE-06 were extensively tested at three different temperatures and up to 1.1 bar pressures. The hyper-crosslinked conjugated polymer EBE-06, formed by the bidirectional bonding of tricarbazole molecules to phosphazene, has a high surface area up to 1987 m 2 /g and a microporosity ratio up to 82%. In addition, 109 cm 3 /g CO2 adsorption and 33 cm 3 /g CH4 adsorption at 273 K and 220 cm 3 /g H2 adsorption was obtained at 77 K. Exceptional selectivity values were calculated for 05/95 CO2 /N2 and reached 442 at 273 K. In addition, the calculation for 05/95 CO2 /CH4 resulted in 121 at 273 K. Most importantly, 15/85 CO2 /N2 selectivity reached 82 at 298 K, which shows that EBE-06 is an excellent candidate for CCUS processes. Graphical Abstract: ga1 Highlights: Cyclotriphosphazene and tricarbazole based microporous hyper-crosslinked conjugated polymer was obtained. EBE-06 was obtained with a specific surface area of 1987 m 2 /g and a micropore ratio of 82%. Exceptional CO2 /N2 selectivity from the IAST calculations reaching 442 with 109 cm 3 /g CO2 adsorption. 220 cm 3 /g H2 adsorption and CO2 /CH4 selectivity up to 121 with 33 cm 3 /g CH4 adsorption. The first example of using hexachlorocyclotriphosphazene molecule with carbazole molecule in the synthesis of HCPs.